2014
DOI: 10.1080/10584587.2014.901882
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of SrFe12O19/ZnFe2O4 Core/Shell Nano-powder Microwave Absorber

Abstract: The nano-powder microwave absorber SrFe 12 O 19 /ZnFe 2 O 4 with core-shell structure were prepared by two-step citrate sol-gel, with analytically pure Fe(NO 3 ) 3 , Sr(NO 3 ) 2 and Zn(NO 3 ) 2 as the main materials. The XRD, TEM, VSM and vector network analyzer were used to analyze the chemical component, structure, morphology and magnetic property of the nano-powder. The results show that when the molar ratio of and SrFe 12 O 19 to ZnFe 2 O 4 is 1:2 and calcined temperature is 850 • C, the composite powder h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Due to increasing need for shielding of electromagnetic wave radiation at frequencies above 1 GHz, one of the most studied high frequency property of hard-soft systems is microwave absorption (i.e., reflection loss)see Section 3.3. Studies on both hard-soft core/shell nanoparticles and nanocomposites have demonstrated that the main parameters of R L can be controlled by the hard/soft ratio [45,91,123,129,271,294,[342][343][344][345][346][347][348][349][350][351][352].…”
Section: A) B)mentioning
confidence: 99%
See 4 more Smart Citations
“…Due to increasing need for shielding of electromagnetic wave radiation at frequencies above 1 GHz, one of the most studied high frequency property of hard-soft systems is microwave absorption (i.e., reflection loss)see Section 3.3. Studies on both hard-soft core/shell nanoparticles and nanocomposites have demonstrated that the main parameters of R L can be controlled by the hard/soft ratio [45,91,123,129,271,294,[342][343][344][345][346][347][348][349][350][351][352].…”
Section: A) B)mentioning
confidence: 99%
“…8), is consistent with the above simple theoretical arguments. In some cases, two-stage loops, typical of spring-magnets, have also been observed [93][94][95]98,114,115,131,190,242,245,261,263,264,266,268,269,271,278,279,[282][283][284][285]289,294,295] (see Fig. 9).…”
Section: Static Magnetic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations